Diversity and endemism in cold waters of the South Atlantic: contrasting patterns in the plankton and the benthos - Boltovskoy, Demetrio (2005)
In total, ca. 7000 zooplanktonic species have been described for the World Ocean. This figure represents less than 4% of the total number of known marine organisms. Of the 7000 zooplanktonic species world-wide, some 60% are present in the South Atlantic; about one third of the latter have been recorded in its Subantarctic waters, and ca. 20% south of the Polar Front. When compared with those of benthic animals, these figures indicate that proportions of the overall inventories that are present in the cold waters are almost two times higher among the zooplankton. In agreement with this pattern, the proportions of Antarctic endemics in the benthos are very significantly higher than those in the plankton. For the water-column dwelling animals, the Polar Front boundary is more important than the Tropical-Subtropical limit, but almost equivalent to the Subtropical-Transitional limit, and weaker in biogeographic terms than the Transitional-Subantarctic boundary. Some of the implications of these dissimilarities, both for ecological theory and for resource allocation strategies, are discussed.